Integration of Pedagogic Knowledge concerning Periodontitis in Clinical Practices: A cross sectional study on Dentists' Implementation - Sania Riaz,; Maaz Asad ,; Muhammad Taqi,; Asaad Javaid,; Nida Tariq,; Fizza Khalid, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the knowledge of dentists regarding periodontitis with its application in their clinical practices. Method: A descriptive cross-sectional study was conducted at Baqai Medical University A content and face validated self administered questionnaire was distributed electronically and physically, and no personal identifying information was collected from the respondents to maintain their concealment and anonymity. All practicing graduate dental practitioners, including general dentists and postgraduates, were approached. The questionnaire was divided into three sections. The first section covered the participants' demographic data, including gender, designation, and clinical experience. In the second section, dentists were given a 3-point Likert scale ranging from disagree, undecided, and agree to mark their knowledge regarding the most prevalent periodontal condition, and it contained seven close-ended questions. The remaining seven close-ended questions in the last section covered the practices and attitudes of dentists, correlating with the knowledge asked in the first section. The responses to practice questions ranged from never, sometimes, and always. The data was analyzed by using a chi-square test. Responses to a three-point Likert scale related to knowledge and practice were recorded. Results: Out of 323 dentists who received the questionnaire, 100% filled the survey form correctly requiring no rejection. With the correlation coefficient, it is understood that there is a positive response to the knowledge of treating periodontitis patients as compared to their clinical implications. Conclusion: It was analyzed that most of the dental clinicians showed profound theoretical knowledge on the subject but regrettably not all of them applied their knowledge to clinical practice for improving patients’ oral hygiene or awareness about the relevant issues. Keywords: Periodontitis, Knowledge, attitude, clinical implication